STAGES OF DEVELOPMENT OF SPECIAL LIGHTING TECHNOLOGIES - Umarova Dildora Bakhtiyarovna; Inoyatov Mirzayor Bakhtiyor ugli (Journals Park Publishing, 2022)
This article deals with lighting, improving the visual sensitivity of objects or ensuring that they are exposed to light-sensitive materials, choosing the right lighting in the construction of houses, providing adequate lighting in individual rooms, and other types of lighting.
Keywords: lighting; objects; appearance